1982
DOI: 10.1007/bf00330360
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of mobile genetic elements in interspecific hybrids of Drosophila

Abstract: In situ hybridization of labeled DNA of four mobile dispersed genetic elements (mdg), isolated from D. melanogaster and C. virilis genomes, with polytene chromosomes of the larvae of several Drosophila species has been carried out. The data show that the mdg elements exhibit a high degree of species specificity. The same conclusions are derived from filter hybridization using 32P-labeled D. melanogaster and D. virilis DNA and cloned mdg sequences immobilized on nitrocellulose filters. We attempted to induce tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
3

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 30 publications
2
31
0
3
Order By: Relevance
“…In Drosophila, gonadal atrophy, mutations and elevated rates of chromosomal breakage have also been observed in interspecific crosses between sibling species (Sturtevant, 1939;Naveira & Fontdevila, 1985). In some of these Drosophila hybrids, germline transposition seems to occur (Evgen'ev et al, 1982;Labrador & Fontdevila, 1994) at a rate similar to those reported previously in dysgenic lines of D. melanogaster (Fontdevila, 1993). The causes of transposition induction in interspecific hybrids are not known but the observation that syndromes characteristic of hybrid dysgenesis are common to both intraspecific and interspecific crosses suggests analogies with this phenomenon.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In Drosophila, gonadal atrophy, mutations and elevated rates of chromosomal breakage have also been observed in interspecific crosses between sibling species (Sturtevant, 1939;Naveira & Fontdevila, 1985). In some of these Drosophila hybrids, germline transposition seems to occur (Evgen'ev et al, 1982;Labrador & Fontdevila, 1994) at a rate similar to those reported previously in dysgenic lines of D. melanogaster (Fontdevila, 1993). The causes of transposition induction in interspecific hybrids are not known but the observation that syndromes characteristic of hybrid dysgenesis are common to both intraspecific and interspecific crosses suggests analogies with this phenomenon.…”
Section: Introductionsupporting
confidence: 79%
“…These data concern the repleta and virilis Drosophila groups in which hybrids were checked only for germinal transpositions and the analyses have been carried out many generations after the hybridization event, sometimes 200 generations after (Evgen'ev et a!., 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila thermotolerance and heat-shock proteins in essence, an independent but related phylad (the montana phylad) replicates the patterns of latitudinal and geographic replacement seen in the virilis phylad. Species within each phylad can be crossed with one another to produce partially fertile progeny; moreover, some species belonging to different phylads can also be crossed (Evgenev et al, 1982;Patterson and Stone, 1952). Second, markers present on each chromosome make possible the introgression of a single chromosome or even a portion of a chromosome bearing, for example, the hsp70 gene cluster, whose location is known (Evgenev et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Although experiments on transcription rates of some TEs seem to demonstrate a response to thermal gradients (Strand and McDonald, 1985), there is not a consensus relative to variations in transposition rates under thermal stresses (Junakovic et al, 1986;Ratner et al, 1992;Arnault et al, 1997). Although spontaneous mobilizations of TEs in laboratory lines may occur 'spontaneously' without any evident explanation (Gerasimova et al, 1985;Biémont et al, 1987), dysgenic crosses (Picard, 1976;Kidwell et al, 1977;Petrov et al, 1995), hybrid crosses (Evgen'ev et al, 1982;Labrador and Fontdevila, 1994;Labrador et al, 1999) and colonization events (Wisotzkey et al, 1997;Labrador et al, 1998;Vieira, 1999;García Guerreiro and Fontdevila, 2001;García Guerreiro et al, 2008) can greatly increase transposition rates of some TEs.…”
Section: Introductionmentioning
confidence: 99%